Grouper Fishery Management Options in the Waters of Mursala Island, Central Tapanuli District, Indonesia - Yenny March Fransisca Harefa; Ronny Irawan Wahju; Domu Simbolon; Muhammad Fedi Alfiadi Sondita (Engineering And Technology Journal, 2024)
Sustainable fisheries are becoming increasingly difficult to achieve due to the decreasing ability of the aquatic environment to support the availability of fish resources [8]. In order to overcome the problem of fishery resource stocks, especially grouper fish, the Indonesian government, in this case the Ministry of Maritime Affairs and Fisheries (KKP), has also issued Decree of the Minister of Maritime Affairs and Fisheries No. 2021 on Grouper Fishery Management Plans in the State Fisheries Management Area of the Republic of Indonesia No. 2021 2021. With regard to the production value of grouper in Central Tapanuli, the availability of specific data on fishing units and operating locations is still not available. Information on the alleged pressure of fishing technology on the condition of the aquatic environment (coral reefs) and grouper fish resources on Mursala Island is still very limited. This means that studies to obtain information related to biological, environmental and technological aspects have a high urgency to be carried out so that they can be synchronized with the area management program of Mursala Island as a KKDP as well as a fishing area. The methods of observation and interviews are more focused on biological and technological aspects and environmental data. The research results show that the fishing activities in the waters around Mursala Island are characterized by fishing activities targeting coral fish with fishing gear in the form of traps, hand lines and arrows. The fish habitat in the form of coral reefs in the waters around Mursala Island has been degraded since 2004. The damage to the coral reefs is caused by the use of destructive methods such as bombs and toxic materials (cyanide).